A new dwarf species, new distribution records, and supplementary descriptive notes of the centipede genus Ityphilus Cook, 1899 (Chilopoda: Geophilomorpha: Ballophilidae) from central Amazonia, Brazil - Pereira, Luis Alberto (Papéis Avulsos de Zoologia, 2012)
A new dwarf species of the centipede genus Ityphilus Cook, 1899, named I. donatellae sp. nov. (Chilopoda: Geophilomorpha: Ballophilidae) is hereby proposed on the basis of specimens from the vicinity of Manaus, Central Amazonia (Brazil), previously identified as Ityphilus calinus Chamberlin, 1957 (hereby designated holotype female, paratype male and paratype female). Supplementary morphological data and new illustrations are provided after this type material. The new species, characterized by having the internal edge of the forcipular tarsungulum serrate, is herein included in a key that will enable the identification of the 10 other Neotropical members of the genus Ityphilus sharing the same trait. New distribution records and supplementary descriptive notes for Ityphilus crabilli Pereira, Minelli & Barbieri, 1994, and Ityphilus demoraisi Pereira, Minelli & Barbieri, 1995 (including the first description of the male of the latter), are also given. Undiluted 2-Phenoxyethanol (CAS No. 122-99-6) has been used as an effective clearing agent/mounting medium for the preparation of temporary mounts of all body parts of the examined specimens.